2019
DOI: 10.1002/mp.13672
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning approaches using 2D and 3D convolutional neural networks for generating male pelvic synthetic computed tomography from magnetic resonance imaging

Abstract: Purpose The improved soft tissue contrast of magnetic resonance imaging (MRI) compared to computed tomography (CT) makes it a useful imaging modality for radiotherapy treatment planning. Even when MR images are acquired for treatment planning, the standard clinical practice currently also requires a CT for dose calculation and x‐ray–based patient positioning. This increases workloads, introduces uncertainty due to the required inter‐modality image registrations, and involves unnecessary irradiation. While it w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 47 publications
4
83
0
Order By: Relevance
“…The proposed eCNN exhibited superior performance to the atlas-based method achieving a MAE of 30.0 AE 10.4 HU and ME of 2.8 AE 10.3 HU for the entire pelvis region while the atlasbased method resulted in a MAE and ME of 64.6 AE 21.2 HU and −0.8 AE 35.4 HU, respectively. Fu et al 49 proposed a similar model to the work of Han 28 where the batch normalization and upsampling layers were replaced with the instance norm and deconvolutional layers. The modified model resulted in MAEs of 40.5 AE 5.4 HU, 28.9 AE 4.7 HU and 159.7 AE 22.5 HU for the whole pelvis, soft-tissue, and bone, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed eCNN exhibited superior performance to the atlas-based method achieving a MAE of 30.0 AE 10.4 HU and ME of 2.8 AE 10.3 HU for the entire pelvis region while the atlasbased method resulted in a MAE and ME of 64.6 AE 21.2 HU and −0.8 AE 35.4 HU, respectively. Fu et al 49 proposed a similar model to the work of Han 28 where the batch normalization and upsampling layers were replaced with the instance norm and deconvolutional layers. The modified model resulted in MAEs of 40.5 AE 5.4 HU, 28.9 AE 4.7 HU and 159.7 AE 22.5 HU for the whole pelvis, soft-tissue, and bone, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering bone extraction accuracy, Fu et al reported a DSC of 0.81 AE 0.04 for bone segmented using an intensity threshold of 150 HU. 49 To facilitate the comparison, the evaluation of bone extraction was repeated using the same intensity threshold where the eCNN model resulted in a DSC of 0.84 AE 0.07, while the original U-Net model led to DSC of 0.71 AE 0.06. Overall, the eCNN method outperformed the atlas-based and original U-Net methods in terms of CT value estimation and tissue delineation.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that the proposed 2D CNN generated the most accurate pelvic sCT images compared to four atlas-based methods (Arabi et al 2018). Fu et al (2019) proposed a 3D CNN that generated more accurate pelvic sCT images than Han's 2D CNN. Generative adversarial networks (GANs) were shown to have better performance in image-to-image translation tasks compared to the corresponding CNNs (Isola et al 2016, Zhu et al 2017.…”
mentioning
confidence: 99%
“…There are sCT algorithms that have been developed for the male pelvis site that use atlas-based, statistical decomposition algorithmic and, voxel-based deep-and machine-learning methods. 16,30,[44][45][46][47] In this study we tested a single commercially available statistical decomposition algorithm-based sCT generator that takes a T 2 -weighted MRI input image. Further testing is required to evaluate the phantoms performance with other sCT methods.…”
Section: Discussionmentioning
confidence: 99%